Hak Penguasaan Tanah Warisan Jero Saren Kauh, Desa Gubug, Tabanan - Slamet Kananda; I Made Suwitra; I Ketut Sukadana (Fakultas Hukum Universitas Warmadewa, 2024)
Heirloom land in Jero Saren Kauh has an important position in the family as inherited land, when one party tries to convert the heirloom land individually, especially in unauthorized ways, it will cause conflict and cause criminal problems. The formulation of the problem in this research is: How is the division of inherited land as heirloom land in Jero Saren Kauh? How is the dispute settlement in the case of control of inherited land as heirloom land in Jero Saren Kauh? The type of research in writing this thesis is empirical legal research with a statutory and conceptual approach. The results of the research show: The division of heirloom land in Jero Saren Kauh was initially carried out individually, so a dispute arose between the heirs. According to the court decision, the certification of heirloom land in Jero Saren Kauh was actually declared invalid registration so that it returned to being heirloom land. Dispute settlement over the certification of heirloom land was initially carried out in a family manner, namely through mediation, but because each party maintained its stance, the plaintiffs filed a lawsuit in court or through litigation.